2015
DOI: 10.1021/acsnano.5b01895
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Bis-urea Nanochannel Architectures Tailored for Single-File Diffusion Studies

Abstract: Urea is a versatile building block that can be modified to self-assemble into a multitude of structures. One-dimensional nanochannels with zigzag architecture and cross-sectional dimensions of only ∼3.7 Å × 4.8 Å are formed by the columnar assembly of phenyl ether bis-urea macrocycles. Nanochannels formed by phenylethynylene bis-urea macrocycles have a round cross-section with a diameter of ∼9.0 Å. This work compares the Xe atom packing and diffusion inside the crystalline channels of these two bis-ureas using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 90 publications
(223 reference statements)
0
31
0
Order By: Relevance
“…3a). Previous work demonstrated that the $0.9 nm diameter nanochannels of the self-assembled phenylethynylene bis-urea host are accessible to gases including Xe and CO 2 [27,30]. The channels can also accommodate a range of organic guests including coumarins, acenaphthylene and stilbenes [21,27].…”
Section: Resultsmentioning
confidence: 99%
“…3a). Previous work demonstrated that the $0.9 nm diameter nanochannels of the self-assembled phenylethynylene bis-urea host are accessible to gases including Xe and CO 2 [27,30]. The channels can also accommodate a range of organic guests including coumarins, acenaphthylene and stilbenes [21,27].…”
Section: Resultsmentioning
confidence: 99%
“…Guillot et al utilized hyperpolarized 3 He and CPMG with gradients to investigate diffusion in aerogel. Hyperpolarized xenon has also been exploited in the investigation of single‐file diffusion effects in small channels, in which adsorbed Xe atoms cannot pass each other . Chen and Hilty used DNP and small flip‐angle PGSTE technique to study suppression of flow motion after the injection of hyperpolarized substance.…”
Section: Hyperpolarized Lnmrmentioning
confidence: 99%
“…Phenylethynylene bis-urea macrocycle 1 was synthesized following a previously reported four-step procedure (Scheme 2.1; sample 1 H and 13 This process was monitored using TGA, which shows a two-step desorption curve between 30 and 130 °C with a weight loss of 18.38% ( Figure 2.3) corresponding to the removal of DMSO.…”
Section: Preparation Of Phenylethynylene Bis-urea Macrocycle Host Fibersmentioning
confidence: 99%